Ablation of ventricular tachycardia by direct left ventricle puncture through a minithoracotomy after double valve replacement: a case report and literature review. Issue 1 (January 2020) - Gao, Ming-Yang; Zeng, Li-Jun; Li, Xue-Xun; Tian, Ying; Su, Pi-Xiong; Yang, Xin-Chun; Liu, Xing-Peng
We herein describe a 33-year-old woman with a mechanical aortic and mitral valve who developed repetitive monomorphic ventricular tachycardia with unstable hemodynamics. Catheter ablation by direct puncture at the left ventricular apex through a minithoracotomy successfully terminated the ventricular tachycardia, which had originated from the apical-septal endocardium in the left ventricle, despite the hindrance to routine access. No procedure-related complications or recurrence of the clinical ventricular tachycardia developed during a 66-month follow-up, demonstrating that endocardial ablation through direct cardiac cavity puncture can be considered in select cases.